Assessing the Impact of Calendar Events upon Urban Vehicle Behaviour and Emissions Using Telematics Data - Junjun Xiang; Omid Ghaffarpasand; Francis D. Pope (Smart Cities)
Employing vehicle telematics data, this study investigates the transport environment across urban and major road networks during a two-week period encompassing the Easter holidays, considered as a case study. The analysis spans four distinct years: 2016, 2018, 2021, and 2022. Geospatial and Temporal Mapping captured the dependencies of vehicle speed, acceleration, vehicle-specific power (VSP), and emission factors (EFs) for air pollutants (CO2 and NOx) on the studied calendar period. The results showed that during the Easter holiday, the median vehicle speeds exceeded annual averages by roughly 5%, indicating a clear deviation from regular traffic patterns. This deviation was particularly stark during the 2021 lockdown, with a significant drop in vehicle presence, leading to less congestion and thus higher speeds and vehicle acceleration. The emissions analyses revealed that individual cars emit higher levels of CO2 and NOx during Easter. Specifically, the median values of CO2 EF and NOx EF were 9% and 11% higher than the annual norm. When combined with road occupancy data, the results demonstrate that the Easter holidays in 2022 had a variable impact on NOx and CO2 emissions, with significant reductions on major roads during weekday rush hours (15–25%) but slight increases on urban roads during weekend periods.